Pattern of firearm injuries managed at rural tertiary centre in Western Uttar Pradesh, North India - Singh, Shailendra Pal; Singh, Pradeep Kumar; Prakash, Manas; Singh, Praveen; Chaudhary, Gyanendra (International Surgery Journal, 2017)
Background: Firearm injuries are associated with substantial emotional, physical and financial burden on community and hospital resources leads to profound morbidity. It is a global public health problem and pose therapeutic challenges to surgeons. Proper management of firearm wounds requires a working knowledge of physical factors involved in the creation of such injuries. Regional variations of the parameters of medico legal aspects of firearm injuries are still lacking. Objective is to analyse pattern of firearm injuries managed at rural tertiary hospital. Methods: All firearm injury cases brought to the emergency department of Hospital, from January 2016 to December 2016 were included in the study. Results: In this study 108 (83.7%) victims were males and 21 (16.3%) were female. Most common age group victimized was 20-29 year (33.3%). Most cases occurred in winter season.113 cases (87.3%) victim were unemployed.81 cases (62.8%) had below intermediate education. 110 (85.3%) cases were of homicidal motive. Shotgun/ ‘kattas’ outnumbered the rifled firearm injuries (109) cases (84.5%). Trunk was involved in 45 cases (34.8%) and lower extremity in (32.6%) 42 cases,) Exit wound found in 93(72.2%) cases only. The fatality rate was 3.9% (5 cases). . Wound debridement was performed for 48 cases (37.2%) of patients, while emergency exploration was done for 30 cases (23.3%). The hospital stay of 49 cases (37.9%) of patients was more than one week. 111 cases (86.1%) were discharged. Conclusions: Addressing the root causes of violence such as poverty, unemployment, substance abuse will reduce the incidence of firearm injuries in our environment. Establishment of efficient emergency health care services for pre-hospital care and effective ambulance system for rapid transport of injured victims to hospital will reduce morbidity and mortality. Management requires knowledge ATLS protocols, mode, presentation and ballistic of firearm. Authorities issuing license for possession of firearms need to be more strict and vigilant.